Evaluation of Maturity Level of IT Cost Efficiency and Its Contribution to Business Profit - Selviana Yunita; Patmawati Hasan; Minarni Minarni; Eka Prasetyaningrum (SISFOTENIKA, 2022)
In order to improve competitiveness, the use of information systems in organizational business prosecesses is mandataory for business people. Agung Mas hotel is one of hotel located in strategic area in Yogyakarakat, with a heritage hotel concept that uphold culture but still provides comfort to customers by implementing information systems in their business processes. In implementation process of information system of Agung Mas Hotel, investment and cost efficiency has not been measured properly. IT governance is needed to determine the extent the used IT in order to achieve the company’s vision and mission. IT governance begins with measuring how well the IT governance is implementes by the company. This study aims to measure the maturity level of the company in IT governance. Balance scorecard is a framework used to assess organizational performance. COBIT and Balance scorecard can provide a parameter from a financial perspective and can be used as a reference for management to make improvments, especially in cost efficiency. The research was conducted by distributing questionnares to hotel employees and then processing the queationnare data to obtain the value of maturity level. Based on the research result, the mean score for PO5 was 2.64 and DS6 was 2.63.